2018
DOI: 10.1371/journal.pcbi.1005877
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Kir4.1 channels and gap junctions account for spontaneous epileptic seizure

Abstract: Experimental recordings in hippocampal slices indicate that astrocytic dysfunction may cause neuronal hyper-excitation or seizures. Considering that astrocytes play important roles in mediating local uptake and spatial buffering of K+ in the extracellular space of the cortical circuit, we constructed a novel model of an astrocyte-neuron network module consisting of a single compartment neuron and 4 surrounding connected astrocytes and including extracellular potassium dynamics. Next, we developed a new model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
(87 reference statements)
1
25
0
Order By: Relevance
“…In addition, it has been shown that downregulation of Kir4.1 channels affects overall ion gradients and also impairs glutamate uptake by astrocytes [12,13]. There are numerous theoretical analyses supporting the spatial relationship between passive and active modulation of [K + ] o by astrocytes and the initiation or maintenance of epileptiform activity [54][55][56]. Furthermore, cell depolarization and impaired ion gradients inhibit glutamate transporter function and cause transporter reversal, thus glutamate release from the cell, which could further affect neuronal excitability [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that downregulation of Kir4.1 channels affects overall ion gradients and also impairs glutamate uptake by astrocytes [12,13]. There are numerous theoretical analyses supporting the spatial relationship between passive and active modulation of [K + ] o by astrocytes and the initiation or maintenance of epileptiform activity [54][55][56]. Furthermore, cell depolarization and impaired ion gradients inhibit glutamate transporter function and cause transporter reversal, thus glutamate release from the cell, which could further affect neuronal excitability [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GJs in astrocytes play a crucial role in ionic regulation; particularly, they can change the concentration of potassium ions. Changes in the strength of GJ coupling can cause neuronal hyperexcitability, and consequently, spontaneous epileptic activity 26 , which ultimately leads to astrocyte uncoupling. Finally, there is evidence that pannexin 1 (Panx1) contributes to the maintenance of epileptic seizures by releasing ATP.…”
Section: Epilepsymentioning
confidence: 99%
“…There is a class of channels that are also specifically expressed on astrocytes: inwardly rectifying potassium channel 4.1 (Kir4.1) (Bataveljic et al, 2012). They play a key role in homeostasis by either net uptake of potassium or by potassium spatial buffering function, loss of which results in seizure susceptibility and epileptogenesis (Du, Li, Chen, Yu, & Wu, 2018;Hinterkeuser et al, 2000;Schröder et al, 2000;Sicca et al, 2016). Striatum astrocytes from HD mouse model have a reduced buffering capacity for extracellular potassium, which may be caused by down-regulation of Kir4.1 and lead to disturbance of glutamate homeostasis, thus resulting in excitotoxic neurodegeneration (Khakh & Sofroniew, 2014).…”
Section: Interactions Between Neurons and Astrocytes In Ndsmentioning
confidence: 99%